HIV surveillance by testing saliva from injecting drug users: a national study in New Zealand - Dickson, N P; Austin, F J; Paul, C; Sharples, K J; Skegg, D C (Journal of epidemiology and community health (1979), 1994)
OBJECTIVE--To determine whether the prevalence of HIV infection among injecting drug users in New Zealand has remained low since the introduction of a needle and syringe exchange scheme in May 1988. DESIGN--Anonymous survey of intravenous drug users attending outlets of the exchange scheme, based on questionnaires and saliva testing. SETTING--Twelve pharmacies and community outreach organisation in six cities. SUBJECTS--Altogether 620 people provided saliva specimens and completed questionnaires. These represented 73% of those who visited exchange scheme outlets during a three month period in 1992. MAIN OUTCOME MEASURE--Saliva was tested for antibodies to HIV-1 and HIV-2 using an IgG-capture enzyme linked immunosorbent assay (GACELISA). RESULTS--Of 591 specimens eligible for inclusion, only three (0.5%) were repeatedly reactive in the GACELISA test, while two of these were also positive in a Western blot test. CONCLUSIONS--Although surveys show that sharing of needles and syringes was common in New Zealand until recently, the prevalence of HIV infection in intravenous drug users has remained low. This can probably be attributed to the success of educational campaigns and legislative action to allow a needle and syringe exchange scheme to be set up.